Efeito nutricional da fortificação protéicoenergética da alimentação escolar de crianças - Prola, Ivo Roberto Dorneles (2013)
In Brazil, as well as in many developing countries, hunger and malnutrition affect a large portion of population. In children, this situation can determine important consequences for the rest of their lives, from both organic and intellectual point of view. But how to ensure adequate food in a world scenario where a sixth of humanity still can not feed themselves in dignity? Among Brazilian Governmental Programs currently in existence, the Brazilian National School Feeding Program - BNSFP stands out for its coverage of the most vulnerable age groups and by combining the fight against both hunger and school drop-out. Due to low financial resources, inclusion of low-cost alternative food has been promoted as a promising strategy. However, the real assessment of the nutritional power of these foods still requires further investigation. Thus, researches that evaluate the inclusion of alternative food supply by the BNSFP should consider not only the economic aspect and acceptance by aimed populations, but the intrinsic nutritional value of the food used. In this context, besides the macronutrient and energy profile, the importance of the amino acid score in the food provided has received prominence in world literature, especially in pediatric patients. In this study, two low cost agro industrial by-products, soybean protein concentrate and broken rice, were used in the formulation of a "mix" with high protein content and amino acid balance appropriate to the high nutritional requirements of growing children. This "mix" was used in food preparations, "Sweet Cookies", of different flavors with great approval by the group of children studied. The experimental foods were added to the school feeding determining significant changes in body composition of participating children: increments in lean mass and decrease in fat mass, especially among children with nutritional problems. Furthermore, this study demonstrated that even being considered the limiting amino acid, lysine present in cooked rice has a high metabolic availability. This finding was made possible by the indicator of amino acid oxidation technique, which had already been previously used for this purpose, but only in the assessment of amino acids of isolated protein sources.